Innovative Technology and Emission Reduction: A Study of the Impact of Green Innovation in Urban East Kalimantan - Rahardi, Muhammad Nur Haswin; Jam'anah, Jam'anah; Paselle, Enos (Dinasti International Journal of Education Management and Social Science, 2025)
This research discusses the impact of innovative technologies and reduction emission through implementation innovation green in urban areas of East Kalimantan, especially in the cities of Samarinda and Balikpapan. The main purpose of this research is to measure the impact of green technology on reducing greenhouse gas emissions, assess the effectiveness of its implementation in the energy and transportation sectors , as well as identify obstacles faced . This study uses​ quantitative descriptive method with survey and in-depth interview approaches. Results study show that application of green technology like system transportation based on electricity, management rubbish technology- based , and renewable energy development give contribution real in reduce emissions and increase quality environment. In addition , innovation green participate push green economic growth and increasing awareness public to issue environment. However, a number of challenge Still faced, such as infrastructure limitations, regulations that are not synchronous , and low awareness and funding . This study recommends the need synergy between governmnt, society and sectors private For strengthen policies and expand green technology implementation for the sake of sustainability environment in East Kalimantan.